Estudo de translação, rotação de eixos, cônicas e quádricas usando autovalores e autovetores - COSTA, David Sousa (2022)
Through this developed work, it is possible to favorably understand the studies on translations, axis rotations, conics and quadrics. The research is based on authors who discuss and describe the studies cited above bibliographically, being of paramount importance the application of mathematical studies in the construction of Mathematics Education, even if abstract, however planned by the student.